Photobiomodulation for pain management during placement of the copper T 380 intrauterine device: Protocol for a randomized, double-blind controlled trial - Anna Carolina Nunes Ferraz; Maria Aparecida Traverzim; Sergio Makabe; Gláucia Gonçalves Abud Machado; Sandra Kalil Bussadori; Raquel Agnelli Mesquita-Ferrari; Cinthya Cosme Gutierrez Duran; Lara Jansiski Motta; Kristianne Porta Santos Fernandes; Anna Carolina Ratto Tempestini Horliana (PLoS ONE, 2026)
Introduction Unplanned pregnancy remains a critical public health issue in Brazil that affects up to 65% of women in some regions and increases the incidence of both unsafe abortions and maternal mortality. Although the copper intrauterine device (IUD) is a highly effective, long-acting contraceptive method, its rate of use remains low in Brazil (only 4.4% of women of reproductive age). One of the primary barriers is the pain experienced during placement of the device, which discourages adherence. Although multiple social and cultural determinants influence IUD uptake, insertion-related pain constitutes a modifiable, procedure-specific factor that may directly affect both pain perception and anticipatory discomfort. Conventional pain management strategies, such as anti-inflammatories and local anesthetics, have produced inconsistent results. Photobiomodulation (PBM) is a non-invasive therapy with anti-inflammatory and analgesic properties that has shown promise in managing pelvic pain in contexts such as labor. Methods and analysis The proposed randomized, double-blind clinical trial will investigate the effectiveness of PBM at reducing pain during the placement of the copper T 380 IUD. Seventy-two women will be randomly allocated to either an active PBM group (n = 36) or sham PBM control group (n = 36). In all participants, the standard IUD placement protocol will follow the guidelines of the Brazilian Ministry of Health. Pain will be assessed using the Visual Analog Scale (VAS) at multiple time points: during each step of insertion (Pozzi clamp, hysterometry, IUD placement) as well as 5 min, 15 min, 24 hours, and 48 hours post-procedure. The secondary outcomes will be analgesic use, anxiety levels (GAD-7), quality of life (WHOQOL-100), satisfaction with the procedure, and adverse effects. Ethics and dissemination. This clinical trial received approval from the Research Ethics Committee of the Mandaqui Hospital Complex (process: 7.367.867) and was registered in ClinicalTrials.gov (NCT06984796). Statistical analyses will be conducted using SPSS v24.0, with a significance level of 5%. Either parametric or nonparametric tests will be applied, depending on the data distribution. Kaplan-Meier curves will be used to assess time to pain resolution. The results will be disseminated through peer-reviewed publications.